Kinetic stabilization of low-oxidation state and terminal hydrido main group metal complexes by a sterically demanding N, N′-bis(2, 6-terphenyl)triazenide. Issue 35 (19th August 2019) - Leverett, Anthony R.; Diachenko, Vera; Cole, Marcus L.; McKay, Alasdair I.
Abstract : Thermally robust main group metal complexes featuring terminal hydride ligands are achieved by deploying a sterically demanding N, N ′-bis(2, 6-terphenyl)triazenide ligand. Abstract : A sterically demanding N, N ′-bis(2, 6-terphenyl)triazenide was employed to stabilize a number of low-coordinate main group metal terminal hydride complexes. These complexes display enhanced thermal stabilities relative to analogous complexes ligated by β-diketiminates, which we attribute to the steric shielding of the metal hydride moiety by the ligand. We also show this triazenide ligand can stabilize low-oxidation state Group 13 metals. DFT calculations conducted on these triazenide ligated Group 13 metal(i ) complexes revealed they possess a narrower HOMO–LUMO gap relative to analogous complexes ligated by other monoanionic N, N ′-ligands. In addition, several heteroleptic Group 13 metal(iii ) and Group 14 metal(ii ) complexes featuring this triazenide are reported.